Population, economic development, and the environment (Oxford, New York, 1994)
The book presents seven distinguished scholars from different fields take up three main themes: The Malthusian conflict, factors underlying fertility changes, and development issues related to the population-environment nexus. They explore in depth the connections between population size nad growth, environmental degradation, and poverty, taking into account the effects of increasing competition for natural resources on social structures. The household unit itself also comes under scrutiny, with the examination of issues such as inequality between the genders, and between children, young adults, and the old
Keywords: Economic development; Environmental aspects